HLA‐DRB3*01:01 is a predictor of immunization against human platelet antigen‐1a but not of the severity of fetal and neonatal alloimmune thrombocytopenia. Issue 3 (26th December 2016) - Wienzek‐Lischka, Sandra; König, Inke R.; Papenkort, Eva‐Maria; Hackstein, Holger; Santoso, Sentot; Sachs, Ulrich J.; Bein, Gregor
Abstract : BACKGROUND: Most cases of fetal and neonatal alloimmune thrombocytopenia (FNAIT) are caused by maternal alloantibodies against human platelet antigen‐1a (HPA‐1a). Alloimmunization mainly occurs in HPA‐1a–negative mothers who are carriers of the HLA‐DRB3*01:01 allele. Recently, it has been reported that the combined presence of HLA‐DRB3*01:01 and HLA‐DRB4*01:01P was associated with severity of FNAIT. We tested this hypothesis by analyzing a large cohort of cases and controls. STUDY DESIGN AND METHODS: In total, 101 mothers with a history of FNAIT caused by anti‐HPA‐1a were investigated. HLA‐DRB1, ‐DRB3, ‐DRB4, and ‐DRB5 genotypes were determined by Luminex technology. Haplotype frequencies were compared between cases and 100 controls. The platelet (PLT) counts of neonates and the incidence of intracranial hemorrhage (ICH) were compared between subgroups defined by genotype. RESULTS: Of the HPA‐1a–immunized mothers, 98% (99/101) carried at least one copy of HLA‐DRB3*01:01. Carriage of HLA‐DRB3*01:01 was significantly associated with immune response to HPA‐1a (odds ratio, 92.3; 95% confidence interval, 26.9‐317.1; p  =  1.34 × 10 −12 ). No association between HLA‐DRB3*01:01 and HLA‐DRB4*01:01P alone or in combination with the PLT count of the newborns or the incidence of ICH was detected. CONCLUSION: In contrast to HLA‐DRB4*01:01P, the inheritance of HLA‐DRB3*01:01 is strongly associated with the propensity for mounting a humoral immune response against fetal HPA‐1a antigen. Neither a homozygous nor a compound heterozygous gene dose predicts the severity of the disease. Testing for the presence of HLA‐DRB3*01:01 might be very useful in counseling women at risk of FNAIT due to anti‐HPA‐1a.